The royal touch made the difference - Abd Razak, Dzulkifli (2006)
AT least twice a year during their reign, the king and queen of Malaysia would light up the Universiti Sains Malaysia campus with not only their regal presence but also their charm. And the royal couple have endeared themselves to both the Malaysian and foreign students and teaching staff of the university. "I have been in this country for two years and I have met your king and queen two times, and shaken hands with the king once." "We come from a far away country where we only see the pictures of our queen in newspapers and magazines; but in Malaysia, I have exchanged words with your queen!" These were among the comments by foreign students. These comments, in a nutshell, was how the USM international community summed up their experiences with the royal couple during their time with the university.